Scope and limitations of learning by projects to develop critical thinking - Castillo Figueredo, Nohora Aidaly; Celis García, Zaida Liliana; Gómez, Sandra Rocío; Agudelo Arango, José Esneider (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article shows part of the result of the use of learning by projects, as a didactic strategy to develop critical thinking in natural sciences from theexecution of a classroom project with the students of the fifth and eighth grades of the Educational Institution “Joaquín González Camargo”. Thisproject was carried out under a qualitative approach, which allowed to review the initial level of critical thinking through a previous questionnaire, following the observation during the implementation of the strategy and the evaluation using the observation guide and the checklist. The group under study was144 students, with whom, once the strategy was applied, it was established within the results that have a level of beginner thinker, being learning byprojects a useful strategy to encourage critical thinking, although there are aspects outside classroom practices that interfere with the process.